Impactos da agroecologia na agricultura familiar e nos Atributos químicos do solo - Carvalho, José Wilson Costa de (Universidade Federal Rural do Semi-Árido, 2010)
Agroecology has emerged as a new paradigm supporting transition processes to more sustainable farming styles. The application of agroecology principles in the family farming has caused a series of transformations in agroecosystems and in various dimensions of family farming. Aiming to study the impacts of Agroecology in the family farming, it was done a study that was based on experiences in rural settlements of Rio Grande do Norte/RN (Brazil), between June, 2009 and June, 2010. The methodology was based on the interpretation of reality through the protagonists´ experiences, the interaction of these subjects with the author knowledge and the theoretical available about this topic. The main techniques were: the semistructured dialogue with a total of 20 interviews; the diagram of impact; the records and observations did in loco , through visits to the experiments; the photographic records made by the author or other individuals involved in the process; as well as the analysis of reports, publications and other institutional archives of the partner entities. The use of Agroecology principles by the family farming has been changing, in many ways, since the relationship between the farmers with their Agroecosystems, providing food production, creating new ways for marketing and income generation, until the overcoming of sexist attitudes on gender relations in family farming, reflecting in the sustainable use of biodiversity, preservation of culture and construction of new knowledge, increasing the production of healthier foods, the construction of autonomy in relation to chemical inputs, the increasing of incomes and the affirmation of new values that are articulated with other flags, as the Agrarian Reform, the Feminism and the Solidary Economy.
Impacts of alternative agriculture in agriculture and the family
Keywords: Agroecology; family farming; participatory methodology; Agroecologia; agricultura familiar; metodologia participativa; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO